Transient hyponatremia of prematurity caused by mild Bartter syndrome type II: a case report - Subhrata Verma; Rahul Chanchlani; Victoria Mok Siu; Guido Filler (BMC, 2020)
Abstract Background Bartter syndrome subtypes are a group of rare renal tubular diseases characterized by impaired salt reabsorption in the tubule, specifically the thick ascending limb of Henle's loop. Clinically, they are characterized by the association of hypokalemic metabolic alkalosis, hypercalciuria, nephrocalcinosis, increased levels of plasma renin and aldosterone, low blood pressure and vascular resistance to angiotensin II. Bartter syndrome type II is caused by mutations in the renal outer medullary potassium channel (ROMK) gene (KCNJ1), can present in the newborn period and typically requires lifelong therapy. Case presentation We describe a case of a prematurely born female infant presenting with antenatal polyhydramnios, and postnatal dehydration and hyponatremia. After 7 weeks of sodium supplementation, the patient demonstrated complete resolution of her hyponatremia and developed only transient metabolic alkalosis at 2 months of age but continues to be polyuric and exhibits hypercalciuria, without development of nephrocalcinosis. She was found to have two pathogenic variants in the KCNJ1 gene: a frameshift deletion, p.Glu334Glyfs*35 and a missense variant, p. Pro110Leu. While many features of classic ROMK mutations have resolved, the child does have Bartter syndrome type II and needs prolonged pediatric nephrology follow-up. Conclusion Transient neonatal hyponatremia warrants a multi-system workup and genetic variants of KCNJ1 should be considered.